Early diagenesis and benthic fluxes of redox-sensitive metals in eastern China shelf sediments - Wang, Xiaojing; Li, Li; Ren, Yijun; Cao, Peng; Zhu, Aimei; Liu, Jihua; Shi, Xuefa (Frontiers in Marine Science, 2023)
Thirteen Short sediment cores (30-50 cm) were collected from Bohai Sea, Yellow Sea and Changjiang Estuary in China, and the early diagenesis of several redox sensitive metals (Fe, Mn, Mo, U and V, referring to as RSMs) in sediment were studied. The recycling process of Mo and Mn was closely correlated with each other, generating benthic fluxes diffusing upward from sediment to overlying water column, and the flux rates are related to the organic carbon oxidation rates. The recycling of U and V were more tightly coupled with Fe oxides, generating benthic fluxes going downward into the sediment in most cores. Significant authigenic accumulation of U, in contrary to little to no accumulation of Mo and V, were found in the study region, even in Changjiang Estuary where hypoxic condition was often found during summer. Benthic diffusive fluxes were compared with authigenic mass accumulate rates (MAR), which indicated that, besides the benthic diffusion process, there are other processes controlling the authigenic accumulation of the RSMs. The close relationships between authigenic accumulation of RSMs with OCburial and OCburial with Sburial, indicating the authigenic accumulation of RSMs is a consequence of redox environment in shelf sediment, which directly influencing the organic carbon degradation process. Compared with other continental margin, moderate enrichment of U was found in China continental sediment. The authigenic U accumulation in BS and NYS sediments accounted for 20 - 68% of the Yellow River input, whilst in SYS sediments accounted for ~ 64% of the Yellow River and Changjiang River input, which acting as important U sinks that cannot be ignored.